Evolution of Dietary Intake Between Before, During and After Ramadan Observance in Tunisian Physically Active Men: A Systematic Review - Boukhris, Omar; Trabelsi, Khaled; Chtourou, Hamdi (International Journal of Sport Studies for Health, 2018)
Objective: The present review was designed to systematize the literature on the evolution of dietary intake in Tunisian physically active subjects (i.e., physically active men and physical education students) between before, during and after Ramadan observance. Evidence Acquisition: Two electronic databases, PubMed and Science direct, were searched using a comprehensive strategy. Studies published prior to August 2018 were included if they assessed dietary intake during Ramadan in Tunisian physically active subjects. A narrative synthesis of findings was conducted. Results: Nine studies evaluated the dietary intake change between before, during and after Ramadan observance. Energy intake decreased in three studies and did not change in six studies. One study showed decreases in fat intake during Ramadan, two studies reported increases and six studies did not report significant changes. Protein intake decreased in three studies, increased in one study and did not change in five studies. Carbohydrate intake did not change in six studies and increased in three studies. Total water intake decreased in four studies and did not change in one study. Conclusions: The literature does not support that Ramadan fasting had adverse effect on dietary intake.